Circadian variation in serum cortisol during hydrocortisone replacement is not attributable to changes in cortisol‐binding globulin concentrations. (2nd February 2016) - Chung, T.T.; Gunganah, K.; Monson, J.P.; Drake, W.M.
Summary: Background: Patients taking hydrocortisone (HC) replacement for primary or secondary adrenal failure require individual adjustment of their dose. In addition to modifying the administered doses of HC for each patient, physicians are increasingly interested in variations in the bioavailability of glucocorticoid replacement. One potential determinant of the bioavailability of replaced HC is a variation in serum cortisol‐binding globulin (CBG) concentration, which may, in turn, affect interpretation of cortisol profiles and individual dose selection for patients on hydrocortisone replacement therapy. Aim: To investigate the hypothesis that there is a circadian variation in CBG levels. Methods and results: A total of 34 male patients divided into 3 groups (10 patients with non‐somatotroph structural pituitary disease on HC replacement, 11 patients with treated acromegaly on HC replacement and 13 patients with treated acromegaly not on HC replacement) and 10 healthy volunteers were included. Cortisol and CBG levels were measured at 6 time points (0800, 1100, 1300, 1500, 1700 and 1900). No significant circadian variation in CBG concentration was found in any of the 4 groups. Conclusion: Circadian variation in serum cortisol during hydrocortisone replacement is not attributable to changes in cortisol‐binding globulin concentration. Changes in serum cortisol levels may thus be explained by other factors including 11 β‐hydroxysteroid dehydrogenase type 1 activity or circadian changes in the binding properties of CBG.